(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The experiment was conducted to compare meat quality parameters between fresh and chilled broiler meat. For this purpose, 30 broilers were chosen from the Meat Research Unit of Animal Science farm of Bangladesh Agricultural University, Mymensingh. The birds were slaughtered and meat characteristics were compared against fresh carcasses and chilled carcasses. The breast of birds was collected to evaluate different physicochemical attributes (color, pH, temperature, shear force value, cooking loss, drip loss, water holding capacity). Significant differences in pH and cooking loss were found in broiler breast meat of fresh carcasses compared to broiler breast meat of chilled carcasses (p>0.05). No significant differences were found in water holding capacity of breast meat between chilled and fresh broiler carcasses (0.05). For color, Lightness (L*) no significant differences were found in breast meat from chilled and fresh carcasses (P> 0.05). Breast meat from chilled and fresh carcasses did not differ significantly in terms of redness (a*). No significant variations (P> 0.05) were identified in the yellowness (b*) of the breast meat from chilled and fresh carcasses. Based on the results obtained from the current study, it may be concluded that chilled broiler meat is better than fresh broiler meat. J Bangladesh Agril Univ 23(4): 542–547, 2025